2010
DOI: 10.1136/jnis.2010.003376
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cone-beam CT and fluoroscopic navigation in treatment of head and neck vascular malformations and tumors

Abstract: This integrated 3D cone-beam CT and fluoroscopic guidance allowed access to deep, difficult to access, locations with ease using a single needle pass in most cases, resulting in improved treatment with decreased procedure times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Some authors have reported achieved accuracies using CBCT guidance in small patient groups to be ,5 mm in most of their cases [9][10][11]13]; however, these groups are small and there is no or little information on the used needle paths. Nonetheless, this suggests that accuracies of around 3 mm can be reached in clinical practice also, irrespective of the complexity of the needle path and the user experience level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported achieved accuracies using CBCT guidance in small patient groups to be ,5 mm in most of their cases [9][10][11]13]; however, these groups are small and there is no or little information on the used needle paths. Nonetheless, this suggests that accuracies of around 3 mm can be reached in clinical practice also, irrespective of the complexity of the needle path and the user experience level.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors described the use of this CBCT with navigational tools in various types of procedures [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Braak et al [8] described the effective patient dose of CBCT guidance procedures to be reduced by 13-42% compared with CT guidance for abdominal and thoracic procedures.…”
mentioning
confidence: 99%
“…The concept of FDCT procedural guidance has been successfully applied with slight variations to percutaneous procedures in the brain, head and neck, and spine 1–3 7 8 10 11 14–16. There are some notable advantages to using FDCT guidance as opposed to conventional CT, including potentially lower radiation doses depending on individual procedure specifics and the fact that a traditional CT room stays functional for diagnostic studies 4 28 29.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated navigational software can be used to plan a needle trajectory and provide real-time guidance for percutaneous procedures throughout the body including for intracranial, spinal, and head and neck procedures 1–3 7 8 10 11 13–15. FDCT allows the performance of complex percutaneous procedures with the safety and convenience of performing these procedures in an interventional suite or hybrid operating room as opposed to a standard CT suite 1–3 8 10 11 15. FDCT data acquired at the time of or during a procedure can additionally be fused with pre-procedure MRI data to allow navigational guidance towards FDCT occult targets 2 16…”
Section: Introductionmentioning
confidence: 99%
“…In [5] the achievable accuracy when targeting head and neck vascular malformations and tumours (including VM, AVM and others in total 65 punctures in 27 patients) under the supervision of intraoperative cone beam CT (CBCT) imaging was investigated. The study demonstrated an available accuracy level of around 2 mm when utilizing CBCT guidance.…”
Section: Figure 1: Fluoroscopic Image Of a Venous Malformation Contrmentioning
confidence: 99%